PENGARUH INTERAKSI TEMAN SEBAYA TERHADAP PERILAKU MEMBOLOS PESERTA DIDIK FASE F DI SMA N 13 PADANG - Nabilahaya, Silfina; Adison, Joni; Solina, Wira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the existence of students who can be influenced by their peers to follow trends or follow modern developments such as truancy while in the school environment, whether or not they are influenced by their peers depends on the individual's perception of their group environment. Because the individual's perception of their peers will determine the decisions they will take later. Based on the problems above, your research aims to describe 1) Peer interaction. 2). Student truancy behavior.3) The influence of peer interaction on truancy. This research uses a quantitative research method of simple linear regression analysis with a population of 179, random sampling technique with a sample size of 124. The instrument used in this research is a statute. Data analysis in this research is percentage and simple linear regression. The results of this study reveal that 1) Peer interaction on truancy behavior in other words the hypothesis is accepted that there is an influence of peer interaction on truancy behavior. 2). Peer interaction on truancy behavior in other words the hypothesis is accepted that there is an influence of peer interaction on truancy behavior in the sufficient category.